Забудова і благоустрій м. Києва в XIX–XX ст. (за документами київських держархівів) - Слюдікова, Т. (Архіви України, 2009)
The process of building of Kiev beginning from the end of XVIII century and formation of its unique architectural air is represented in the article on the basis of the archival records.